A giant within Carpocorini (Hemiptera: Heteroptera: Pentatomidae): Description of Adustonotus graziae sp. nov. - Bianchi, Filipe Michels (Zootaxa, 2021)
The Carpocorini are distributed worldwide, and it is one of the most speciose tribes within the Pentatomidae with 127 genera and more than 500 valid species. Recently, Adustonotus Bianchi was described to contain eight species formerly placed within Euschistus Dallas. Among them, Adustonotus grandis (Rolston) and Adustonotus latus (Dallas) are remarkable for their large size. Herein, the phylogenetic position of a new taxon is inferred by a total evidence analysis based on 85 morphological characters and four molecular markers. Adustonotus graziae sp. nov. is described, and is recovered in a polytomic lineage, including A. grandis and A. latus. These species share a solid combination of features that enable them to be separated from the other Adustonotus species (e.g., large size, the humeral angles spatulate and exceptionally produced, and the capsula seminalis shortened). Illustrations of external and internal genitalia, and a distributional map are provided.